Investigating the role of abscisic acid and its catabolites on senescence processes in green asparagus under controlled atmosphere (CA) storage regimes - Anastasiadi, Maria; Collings, Emma R.; Terry, Leon A. (Elsevier, 2022)
Asparagus (Asparagus officinalis) is a highly perishable crop with a short postharvest life. Although some research has been done on the application of controlled atmosphere (CA), it has not been sufficiently explored and the underlying mechanisms controlling asparagus senescence processes are not well understood, restricting its potential for commercial application. The aim of this study was to investigate for the first time the link between abscisic acid (ABA) and ABA catabolites and senescence in asparagus stored under a range of different CA conditions. Two different set-ups were run in parallel; a traditional CA delivered by an International Controlled Atmosphere (ICA) system with continuous gas supply and LabPods™ fitted with sensors for real time monitoring of respiration rate (RR) and respiratory quotient (RQ) and able to retain established CA conditions with minimum gas supply requirements. The role of genetic variability was also studied by including two UK grown asparagus cultivars ‘Gijnlim’ and ‘Jaleo’ adapted for different climatic conditions. The results indicated that ABA and its catabolites were present in significantly higher concentrations in the air stored spears (control) compared to CA throughout storage, irrespective of cultivar, and were associated with accelerated senescence processes observed in control samples, such as textural changes indicative of spear toughening, discolouration, sugar depletion and asparagine accumulation. Furthermore, partial least squares regression (pls-r) applied for both cultivars, successfully differentiated samples based on O2 and CO2 concentrations and storage duration, both in cold storage and during shelf-life with the separation being driven primarily by ABA and its catabolites. Physiological and biochemical results indicated that all three CA conditions tested ([CA1] 2.5% O2, 3% CO2, [CA2] 2.5% O2, 6% CO2 and [CA3] 2.5% O2, 10% CO2) successfully retained quality parameters including texture, colour, moisture content and visual appearance longer compared to air (control); however, they did not completely suppress the development of ‘tip-breakdown’ (a physiological disorder also known as tip rot) towards the end of storage, which coincided with rising concentrations of phaseic acid indicating an activation of the abscisic biosynthetic and catabolic pathway. It can be concluded that CA conditions can delay senescence for at least 3-weeks (2 weeks cold storage and 1 week shelf-life), by lowering metabolic rate and respiratory quotient (RQ) within the spears compared to control, and through successfully regulating ABA biosynthetic and catabolic pathways.
Keywords: Asparagus officinalis; Abscisic acid (ABA); Sugars, ABA catabolites